基于Pro/E的空间分度凸轮精确建模与加工 - 张俊; 刘亚丽 (Jixie chuandong)
The centerline trajectory equations of the rotation axis of spatial indexing cam follower roller are established,the theoretical contour curves are obtained by using "from equation" and "thicken" tool of Pro/E software.The three dimensional digitization precise modeling of spatial indexing cam is finished.The machining and simulation of the spatial indexing cam groove is carried out by using the four-axis trajectory machining schema in Pro/NC module.The efficiency and accuracy of the manufacture is improved.